Early Risk Factors for Retinopathy of Prematurity in Very and Extremely Preterm Chinese Neonates - Huang, Hai-Bo; Chen, Yi-Hua; Wu, Jing; Hicks, Matt; Yi, Yan-Zhi; Zhang, Qian-Shen; Chow, Chun-Bong; Cheung, Po-Yin (Frontiers in Pediatrics, 2020)
Objective: To investigate the incidence and risk factors of retinopathy of prematurity (ROP) in very and extremely preterm (28+0-<32+0 and <28+0 weeks gestation, respectively) neonates, and the predictive factors for ROP in the early hours after birth and during hospitalisation. Methods: Using a prospective database supplemented with retrospective chart review, we identified preterm neonates born at gestation <32 weeks at the University of Hong Kong-Shenzhen Hospital between January 2015 and August 2018. Demographic and clinical variables were studied including indicators of disease acuity in the first 24 hours after birth. We also compared the difference in risk factors between survivors with ROP and survivors without ROP. Results: During the study period, there were 529 preterm neonates admitted to our neonatal intensive care unit with 120 (23%) born at <32 weeks gestation. Thirteen (11%) neonates died. Among the 107 survivors, 23 (21%) had ROP, of whom 5 (22%) received laser and/or medical therapy for severe ROP. Compared with survivors without ROP, infants with ROP had lower mean blood pressure in the first 12 and 24 hours after birth, respectively. Using multi-variate regression, gestation age, mean blood pressure in the first 12 hours after birth, hospital length of stay, and total days of blood gases pH<7.2 were independent risk factors for ROP. Conclusions: In this small cohort of Chinese neonates born <32+0 weeks gestation, survivors with ROP had lower blood pressure in the early hours after birth, younger gestation, longer hospital stay and duration of acidosis when compared to those without ROP.